A computer-controlled Gerdien atmospheric ion counter - Aplin, K; Harrison, R (2000)
Accurate measurements of atmospheric ions are desirable in order to investigate atmospheric aerosol processes. A cylindrical capacitor ion counter is described which has a flexible computerized control system, to allow selection of ion mobility by changing the bias voltage across the capacitor. Ion measurements obtained correlate well with the ionization rate measured with an adjacent Geiger counter in clean air. Measurements of air ions using the device in current and voltage decay modes show consistent results. The collecting electrode is exposed directly in the air stream to be sampled, eliminating diffusive losses in intake tubes. The system can measure ion concentrations from 20 ions cm-3 (including typical atmospheric concentrations) and can sample ions rapidly. These characteristics enable comprehensive air conductivity measurements to be made. © 2000 American Institute of Physics.